A pictorial key to the species of the Aedes (Zavortinkius) in the Afrotropical Region (Diptera: Culicidae) - Huang, Yiau-Min; Rueda, Leopoldo M. (Zootaxa, 2015)
Six species of the subgenus Zavortinkius of Aedes Meigen in the Afrotropical Region are treated in a pictorial key based on diagnostic morphological features. Images of the diagnostic morphological structures of the adult thorax and leg are included.